(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2014)
I provide empirical evidence from a longitudinal cross-cultural reader reception survey showing that cultural outsider (French) and insider (New Zealand) readers are differently influenced by the geographically and culturally-situated elements in Utu (French 2004, English translation 2011), a crime novel set in contemporary New Zealand by French writer Caryl Férey. After reading the novel, both cultural outsider and insider readers changed their opinions towards the image portrayed by Férey, even when his cultural claims were incorrect. Furthermore, for French readers, this influence extended beyond Utu’s final page to opinions about New Zealand and its inhabitants.